2022
DOI: 10.1038/s41422-022-00735-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting UHRF1-SAP30-MXD4 axis for leukemia initiating cell eradication in myeloid leukemia

Abstract: Aberrant self-renewal of leukemia initiation cells (LICs) drives aggressive acute myeloid leukemia (AML). Here, we report that UHRF1, an epigenetic regulator that recruits DNMT1 to methylate DNA, is highly expressed in AML and predicts poor prognosis. UHRF1 is required for myeloid leukemogenesis by maintaining self-renewal of LICs. Mechanistically, UHRF1 directly interacts with Sin3A-associated protein 30 (SAP30) through two critical amino acids, G572 and F573 in its SRA domain, to repress gene expression. Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Hu et al. ( 50 ) demonstrated that SAP30 can interact with UHRF1 to promote the activation of the MYC signaling pathway and abnormal self-renewal of leukemia-initiating cells, resulting in the occurrence and development of acute myeloid leukemia and poor prognosis. The E2F family affects cell cycle progression, apoptosis, differentiation, and DNA damage repair ( 51 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al. ( 50 ) demonstrated that SAP30 can interact with UHRF1 to promote the activation of the MYC signaling pathway and abnormal self-renewal of leukemia-initiating cells, resulting in the occurrence and development of acute myeloid leukemia and poor prognosis. The E2F family affects cell cycle progression, apoptosis, differentiation, and DNA damage repair ( 51 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…There was also an enrichment for the hallmark apoptosis pathway in VcKO TPT DPs with Mxd4 mRNA, encoding for a Myc antagonist that inhibits leukemogenesis, topping the list of DEGs (Fig. 4G) (Hurlin et al, 1996) (Hu et al, 2022). Among the other notable DEGs were Fos, Dusp1 and Tet2, which may explain one mechanism by which competition may regulate gene expression to promote survival (Fig.…”
Section: Inter-thymocyte Competition Suppresses T-all Development Fro...mentioning
confidence: 97%
“…The second network included three proteins and is referred to as the NuRD complex. Two of these proteins function as deacetylases (SAP30, MTA2), and the proteins in this network modulate the effects of both p53 (MTA2) and STAT3 (GATAD2A) (Tables S7 and S8) [84,85]. The NuRD complex is a chromatin remodeling complex [86,87].…”
Section: Comparison Of Phosphoproteomic Profiles For Fab-m4/m5 Cells ...mentioning
confidence: 99%